2013
DOI: 10.1089/ten.tea.2012.0631
|View full text |Cite
|
Sign up to set email alerts
|

Prevascularization of a Gas-Foaming Macroporous Calcium Phosphate Cement Scaffold Via Coculture of Human Umbilical Vein Endothelial Cells and Osteoblasts

Abstract: The lack of a vasculature in tissue-engineered constructs is currently a major challenge in tissue regeneration. There has been no report of prevascularization of macroporous calcium phosphate cement (CPC) via coculture of endothelial cells and osteoblasts. The objectives of this study were to (1) investigate coculture of human umbilical vein endothelial cells (HUVEC) and human osteoblasts (HOB) on macroporous CPC for the first time; and (2) develop a new microvasculature-CPC construct with angiogenic and oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 64 publications
1
38
1
Order By: Relevance
“…Several studies showed that coculturing endothelial cells with osteoblasts-like cells resulted in the formation of microcapillary-like structures similar to those observed in vivo [17,18]. Although CPC is promising for bone repair due to its excellent biocompatibility and bone replacement capability, little has been reported on prevascularization of CPC, with only one report on coculturing endothelial cells and osteoblasts to prevascularize CPC [23]. The coculture could promote the self-assembled organization of the microcapillary-like structures.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies showed that coculturing endothelial cells with osteoblasts-like cells resulted in the formation of microcapillary-like structures similar to those observed in vivo [17,18]. Although CPC is promising for bone repair due to its excellent biocompatibility and bone replacement capability, little has been reported on prevascularization of CPC, with only one report on coculturing endothelial cells and osteoblasts to prevascularize CPC [23]. The coculture could promote the self-assembled organization of the microcapillary-like structures.…”
Section: Discussionmentioning
confidence: 96%
“…Another study used starch-based scaffold to coculture osteoblasts and endothelial cells and obtained microcapillary-like structures [17]. However, a literature search revealed no report on prevascularization of CPC, except our recent study on coculture of endothelial cells and osteoblasts on CPC without biofunctionalization [23], in which cell attachment was not robust.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing tridimensional co-cultures embedded in a variety of scaffolds may improve our knowledge of bone remodeling and possibly enable future clinical application (Brennan et al, 2013;Deb et al, 2010;Dorst et al, 2014;Gao et al, 2014;Hofmann et al, 2008;Santos et al, 2009;Thein-Han & Xu, 2013). In particular, co-cultures within scaffolds under proper environmental stimuli have been proposed to explore the interaction of ECs with other cell types already seeded in the scaffold or attracted by the surrounding implanted (hosting) tissue.…”
Section: Integrating the System: 2d And 3d Co-culturesmentioning
confidence: 99%
“…In the last few years, research has been prompted to develop increasingly complex 3D culture systems in bioreactors, where cells are seeded on proper scaffolds and stimulated so as to mimic the physiological conditions more accurately. These bioreactors aim at enabling bone regeneration by incorporating different cells types, such as osteoblasts and endothelial cells (ECs), into bioinspired materials within a surveilled habitat (Brennan, Davaine, & Layrolle, 2013;Deb, Mandegaran, & Di Silvio, 2010;Dorst, Oberringer, Grässer, Pohlemann, & Metzger, 2014;Gao et al, 2014;Hofmann et al, 2008;Santos et al, 2009;Thein-Han & Xu, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods to fabricate porous TECs from natural or synthetic polymers include gas foaming [62, 63], particulate leaching [52, 64, 65], or freeze-drying [50, 66]. While these methods are effective in creating porous scaffolds, they lack the control necessary to create specific architectures.…”
Section: D Bone Modelsmentioning
confidence: 99%